Rintisan Alat Bantu Opent Shoulder Trainer Aparatus Lantai Untuk Melatih Gerakan Handstand Pada Cabang Olahraga Senam Artisitik - Kafrawi, M Firdaus; Wismanadi, Himawan; Julianto, Julianto (Universitas Negeri Surabaya, 2024)
Every sports organization will be sustainable with aspects of the main achievement supporting components one of which is performance effectiveness with this pilot research on open shoulder trainer tools by developing existing products, validating and testing the effectiveness of the product resulting from this development is expected to be able to support the implementation of activity facilities and infrastructure coaches in performance activities teaching handstand movements to children under the age of adulthood in artistic gymnastics. The purpose of this research is to develop an existing product, validated by experts, and tested to find out how effective the product is to support the achievement of the trainer's activities for gymnasts in learning that initially did not use assistive devices, namely the old method is called the control group while the method group with the latest teaching is called the experimental group. then the two groups were given a pre-test or observation to find out their abilities were the same or not significantly different. The results of this study indicate that the average data obtained shows that the performance of the new system is much higher than the old system. The average performance of the old system = 48%, and the new system is 78%. Working speed of the old system = 57% and 75% of the new system. The comfort of the old system = 50% and the new system is 85%. Based on these data it can be seen that the new work system can increase the average system performance by 30%, work speed by 18%, work comfort by 35%, and work productivity by 25%.